Peroxisomal Enzymes and 8-Hydroxydeoxyguanosine in Rat Liver Treated with Perfluorooctanoic Acid. Issue 1 (12th June 2013) - Abdellatif, Awad; Al-tonsy, Ahmad H.; Awad, Mahmoud E.; Roberfroid, M.; Khan, M. Nezam Ullah
Abstract : Although peroxisome proliferators are considered non-genotoxic agents, most of them, nevertheless, were found to promote and/or induce, hepatocellular carcinoma (HCC) in rodents. The aim of the present study is, first, to investigate whether the peroxisome proliferator perfluorooctanoic acid (PFOA) possesses inherent liver cancer promoting activity, and second, to study the possible mechanisms involved. To acheive these aims two protocols have been applied, a biphasic protocol (initiation by diethyl-nitrozamine (DEN) 200 mg/kg i.p. followed by treatment with 0.005% or 0.02% perflourooctanoic acid (PFOA) for 14 and 25 weeks) and a triphasic initiation, selection-promotion (IS) protocol (initiation by giving 200 mg/kg DEN i.p. followed by a selection procedure for 2 weeks consisting of giving 0.03% 2-acetylaminofluorene (2-AAF) in diet). In the middle of this treatment a single oral dose of carbon tetrachloride (2.0 ml/kg) was given, followed by giving diet containg 0.015% of PFOA for 25 weeks. After applying both protocols, our results showed slight increase in the catalase activity while acyl CoA oxidase activity was markedly increased. Both experiments indicated that PFOA has a liver cancer promoting activity. Other groups of rats were given either basal diet or diet containing 0.02% PFOA. Five or nine weeks later they were sacrificed and the levels of 8-hydroxydeoxyguanosine in the isolated DNA were estimated. The data showed a slight nonetheless insignificant increase in 8-hydroxydeoxyguanosine. From the present data, it is concluded that PFOA is a true liver cancer promoter that may not require extensive initial DNA damage for its promoting activity.